MRSI: Mobile Road Safety Information Application using Crowdsourcing - Mohamad Safuan, Johari; Hamizan, Sharbini; Po Chan, Chiu; Noor Hazlini, Borhan; Hui, Zhao (Akademia Baru Publishing, 2026)
Road deterioration poses a significant challenge for all. Enhancing road security and minimizing accidents necessitates an effective, dependable tool to assist road users, particularly in UNIMAS and Kota Samarahan. Presently, a gap exists as there is no intuitive application available to offer and report on road traffic information. The development of an app to communicate road conditions and safety is therefore essential. With the growing preference for smartphones over traditional desktops or notebooks, leveraging these devices for rapid dissemination and notification about road status and safety proves to be a more time-efficient and convenient method. Test results indicate that over 70% of users found the application to be user-friendly with stable functionality. Additionally, the app provides real-time traffic condition updates.